Del margen al centro: comentarios sobre precedentes históricos en relación al acceso e inclusión en las escuelas públicas de los Estados Unidos = From the margin to the center: Commentaries about historical precedents related to access and inclusion in the public schools of the USA - Grinberg, Jaime G. A. (Educação, 2009)
Public schools evolved in the USA during the XIX century under the premise of providing equal opportunity in education to all, regardless of family background, social class, or economic resources. Merit, success and achievement would depend on the individual student and will not depend on any other variables except the pupil’s dedication, hard work, intelligence, and ability to perform. If according to the expectations, the system would fail to provide equal opportunity, resources, and equity in programs, resources, curricula and pedagogy, then the system would be failing the premises and expectations of its creation as well as the ideological signifier of Americanization. This enabled to take-on the system ideologically and legally. Commenting on historical precedents, the paper discusses how schools contributed to the ideological hegemonizing process of Americanization, which did not include diversity and difference, but it rather contributed to marginalize and to the homogenization of its curricula, both in practice and in its organization. However, the interruptions and challenges presented by not fulfilling the ideological and legal premises, contributed to redefine the national ethos in order to accommodate and expand Americanization into an ideology of national inclusion. The paper also comments on historical and contemporary tensions